Ambassadors, stewards, advocates—Is engagement of polar tourists in conservation symbolic or substantive? A scoping review - Reas, Julianne; Leung, Yu-Fai; Cajiao, Daniela (Frontiers in Sustainable Tourism, 2023)
The continued growth of polar tourism is causing increasing concerns about its potential environmental effects, invigorating the current discourse about tourism's role in the sustainable future of the Polar Regions. These concerns are often met with the industry's narratives on purported positive impacts of polar tourists who would become ambassadors, stewards or advocates. However, the extent to, and the ways in which these three seemingly interchangeable 'ambassador' terms have been used or examined in the scientific literature are largely unknown. To address this gap, we traced the definitions of these terms and identified 16 peer-reviewed studies that incorporated the terms in two types of study design: 1) discussing the terms in the context of investigating relationship and influential factors of tourists' motivations, experiences, behavior intentions, and behavior; and 2) examining the terms as ethical imperatives or normative concepts. Results of this scoping review provides a clearer picture of how the 'ambassador' terms are defined and utilized in polar tourism research, and points to the needs for further understanding, conceptualization, and operationalization of the related concepts beyond focusing on tourists themselves as ambassadors.